(3cJGH ejOGf GdYbds - (3LGHQ Hf MjGf Hf YHO Gddg Gdchaj, CHh ehSi, J (B200 (3g` s ((3eOjfI MjOQ s)
(3ChdgG (B:s
(3Chd GdehLhO efg bhdg (B: (3YdjgG GdejRGf Ch ebOGQ eG jMJed GdLhgQ ai cd YGde ef gPg GdYhGde hGdChd CUd GdKGfi s
(3BNQgG (B:s
(3bGd HdjfGS ai hUaI dcJGHg Yde SQGFQ GdNdjbI hVYI GdWHjYI Je cJGH ejOGf GdYbd s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdJGSYs
(3HgG fXGe GdJYbjHIs
(3JHUQGJ GdCUd (B:s
(3GdfSNI fGbUI GdChd s
(3eUOQ GbJfGA GdCUd (B:s
(3ShQjG (B(9318) s
Keywords: (3GdadSaI hGdefWbs